Clinical Outcomes for Reconstruction of the Posterolateral Corner and Posterior Cruciate Ligament in Injuries With Mild Grade 2 or Less Posterior Translation: Comparison With Isolated Posterolateral Corner Reconstruction. (July 2013) - Kim, Sung-Jae; Lee, Su-Keon; Kim, Sung-Hwan; Kim, Seong-Hun; Jung, Min
Background: There have been no previous studies showing clinical outcomes according to treatment options of posterior cruciate ligament (PCL) injury with mild grade 2 or less posterior translation (<7 mm) combined with posterolateral rotatory instability. Purpose: To compare the clinical outcomes of posterolateral corner (PLC) reconstruction with or without simultaneous PCL reconstruction in PCL injuries with mild posterior translation. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 46 patients with a PCL injury with mild posterior translation combined with posterolateral rotatory instability were retrospectively reviewed. Twenty-two patients had undergone isolated PLC reconstruction (group A), and 24 patients had undergone simultaneous reconstruction of the PCL and PLC (group B). Each patient was assessed for knee instability with the dial test at 30° and 90° as well as with varus and posterior stress radiography and were evaluated with the Lysholm knee score and International Knee Documentation Committee (IKDC) subjective and objective grading. Results: In all cases, the minimum follow-up period was 24 months. At the final follow-up evaluation, no significant side-to-side difference was found on varus stress radiography (group A, 1.55 ± 0.78 mm vs group B, 1.35 ± 1.00 mm; P = .458) or the dial test (at 30°: group A, 4.00° ± 1.83° vs group B, 4.04° ± 1.30°; P = .929; at 90°: group A, 3.64° ± 1.18° vs group B, 3.67° ± 1.37°; P = .937). However, group B showed a significant improvement compared with group A on posterior stress radiography (group A, 0.16 ± 0.44 mm vs group B, –1.44 ± 0.74 mm; P < .001), Lysholm knee score (group A, 18.36 ± 8.73 vs group B, 23.42 ± 7.44; P = .040), IKDC subjective score (group A, 25.51 ± 7.11 vs group B, 33.08 ± 5.89; P < .001), and IKDC objective score (group A preoperatively: grade C = 19 patients, grade D = 3; group B preoperatively: grade C = 20, grade D = 4; group A postoperatively: grade B = 11, grade C = 11; group B postoperatively: grade A = 12, grade B = 9, grade C = 3) ( P < .001). Conclusion: Simultaneous reconstruction of the PCL and PLC is recommended when addressing PCL injuries with mild grade 2 or less posterior translation combined with posterolateral rotary instability.